1978
DOI: 10.1055/s-0038-1646664
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Tests for Measurement of Cell Integrity

Abstract: SummaryVarious tests were evaluated for their capacity to differentiate between platelet suspensions with different degrees of cell damage. Those suspensions were prepared by simultaneous isolation of platelets from the same platelet-rich plasma (PRP) using the following procedures:1. centrifugation at 4°C with EDTA2. gel filtration in Tangen’s buffer3. gel filtration in Ca2+-free Tyrode’s solution4. gel filtration in Ca2+-free Tyrode followed by dehydration against polyethylene glycol 20,000 and5. albumin den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…A contribution of other additional factors to elevated LDH levels in PNH should not be overlooked. For example, other non-hemolytic clonal diseases, such as myelodysplatic syndromes, present elevated LDH, which appears to be an important prognostic marker [28], and LDH is a known marker of tissue and cell injury [29]. Whilst hemolysis is common to HS, PNH and SCD, we found cell adhesive functions to vary between diseases.…”
Section: Discussionmentioning
confidence: 89%
“…A contribution of other additional factors to elevated LDH levels in PNH should not be overlooked. For example, other non-hemolytic clonal diseases, such as myelodysplatic syndromes, present elevated LDH, which appears to be an important prognostic marker [28], and LDH is a known marker of tissue and cell injury [29]. Whilst hemolysis is common to HS, PNH and SCD, we found cell adhesive functions to vary between diseases.…”
Section: Discussionmentioning
confidence: 89%
“…Measurement of the specific radioactivity of the various spots confirmed that the 32p measurement was a true reflection of the quantities of the various fractions [10]. Spectrophotometric analysis of Fru-2,6-P 2 was carried out according to the method of van Schaftingen et al [13] in alkaline extracts of gel-filtered platelets as well as in extracts of concentrated platelet suspensions obtained by repeated centrifugation-resuspension in EDTA-containing Ringer solution [14].…”
Section: Incubation Studiesmentioning
confidence: 89%
“…The platelets washed with acid citrate exhibit hardly any pseudopods. Besides their functional integrity, the platelets washed with acid citrate thus exhibit ultrastructural features (1,13,28,31) which also indicate maintenance in morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of pseudopod formation proved to be one of the most sensitive tests of platelet integrity (1). The platelets washed with acid citrate exhibit hardly any pseudopods.…”
Section: Discussionmentioning
confidence: 99%